CONCESSION POLICY IN THE TRANS-SFSR (1921-1930) - Archil Kokhreidze; Ia Tutashvili; Nodar Shoshiashvili (International Journal of Innovative Technologies in Social Science, 2024)
Today, Georgia strives to take a worthy place in the world, develop its economy, establish close business ties with some important countries and attract investments. In view of this, we consider it relevant to identify and analyze the archival materials relating to the experiences of our region in the field of business relations with other countries in the 20s of the twentieth century. The object of the study is the concession policy of Bolsheviks and how worked the concession institutions from a historical perspective. The purpose of this study to present the concession agreements as a mechanism for partnership between social, state and private elements, that ensured sustainable economic development of the TSFSR as a whole and of Georgia in particular. It is also important to research the emergence, development and abolition of concessions, as well as to bring to light the activities of central and local governments bodies. Economic review of concessions will make it possible to take into account the experience gained in the historical past when developing, adapting and introducing the modern forms of economic relations. The study of these experiences will inevitably be conducive to concessional ties with other countries at the current stage of economic development. Problem Identification. Studying the economic retrospective of concessions makes it possible to take into account previous experience when developing, adapting and implementing modern forms of economic cooperation. Studying this experience will facilitate the implementation of the concession cooperation plan at the current stage of economic development.